Philosophies of arts: An essay in differences - Kivy, Peter 1934-2017 (Cambridge Cambridge University Press, 1997)
Since the beginning of the eighteenth century the philosophy of art has been engaged on the project of trying to find out what the fine arts have in common and, thus, how they might be defined. Peter Kivy's purpose in this accessible and lucid book is to trace the history of that enterprise and argue that the definitional project has been unsuccessful. He offers a fruitful change of strategy: instead of engaging in an obsessive quest for sameness, let us explore the differences between the arts. He presents five case studies, three from literature, two from music. With its combination of historical and analytic approaches this is a book for a wide range of readers in philosophy, literary studies, music, and non-academic readers with interests in the arts.